La enfermera instrumentista - García Castrillón, Laura (2018)
The operating room nurse must acquire basic concepts and fundamentals of the surgical environment, environmental aspects, and role of the human team, patient safety, anes-thesia, equipment, instruments, sutures and basic nursing care that will be applied to the surgical patient. The fundamentals will be general and applicable to all surgical processes and all types of patients; the theoretical aspects must be accompanied by a thorough training in skills, prior to professional practice in any surgical specialty. The academy, in addition to the basic training, must offer specialized training to the operating room staff, through training in services and/or surgical simulation. Teaching experience that facilitates professional development and the improvement of healthcare quality is vital.